A scoping review for building a criticality-based conceptual framework of altered states of consciousness - Gervais, Charles; Boucher, Louis-Philippe; Villar, Guillermo Martinez; Lee, UnCheol; Duclos, Catherine (Frontiers in Systems Neuroscience, 2023)
The healthy conscious brain is thought to operate near a critical state, reflecting optimal information processing and high susceptibility to external stimuli. Conversely, deviations from the critical state are hypothesized to give rise to altered states of consciousness (ASC). Measures of criticality could therefore be an effective way of establishing the conscious state of an individual. Furthermore, characterizing the direction of a deviation from criticality may enable the development of treatment strategies for pathological ASC. The aim of this scoping review is to assess the current evidence supporting the criticality hypothesis, and the use of criticality as a conceptual framework for ASC. Using the PRISMA guidelines, Web of Science and PubMed were searched from inception to February 7th 2022 to find articles relating to measures of criticality across ASC. N=427 independent papers were initially found on the subject. N=378 were excluded because they were either: not related to criticality; not related to consciousness; not presenting results from a primary study; presenting model data. N=49 independent papers were included in the present research, separated in 7 sub-categories of ASC: disorders of consciousness (DOC) (n=5); sleep (n=13); anesthesia (n=18); epilepsy (n=12); psychedelics and shamanic state of consciousness (n=4); delirium (n=1); meditative state (n=2). Each category included articles suggesting a deviation of the critical state. While most studies were only able to identify a deviation from criticality without being certain of its direction, the preliminary consensus arising from the literature is that non-rapid eye movement (NREM) sleep reflects a subcritical state, epileptic seizures reflect a supercritical state, and psychedelics are closer to the critical state than normal consciousness. This scoping review suggests that, though the literature is limited and methodologically inhomogeneous, ASC are characterized by a deviation from criticality, though its direction is not clearly reported in a majority of studies. Criticality could become, with more extensive research, an effective and objective way to characterize ASC, and help identify therapeutic avenues to improve criticality in pathological brain states. Furthermore, we suggest how anesthesia and psychedelics could potentially be used as neuromodulation techniques to restore criticality in DOC.